Oriented polyvinylidene fluoride–trifluoroethylene (P(VDF–TrFE)) films by Langmuir–Blodgett deposition: a synchrotron X-ray diffraction study. Issue 43 (16th October 2015) - Lindemann, W. R.; Philiph, R. L.; Chan, D. W. W.; Ayers, C. T.; Perez, E. M.; Beckman, S. P.; Strzalka, J.; Chaudhary, S.; Vaknin, D.
Abstract : Langmuir–Blodgett films of polyvinylidene fluoride trifluoroethylene – P(VDF–TrFE)-copolymers possess substantially improved electrocaloric and pyroelectric properties, when compared with conventionally spin-cast films. Abstract : Langmuir–Blodgett films of polyvinylidene fluoride trifluoroethylene – P(VDF–TrFE)-copolymers possess substantially improved electrocaloric and pyroelectric properties, when compared with conventionally spin-cast films. In order to rationalize this, we prepared single-layered films of P(VDF–TrFE) (70 : 30) using both deposition techniques. Grazing incidence wide-angle X-ray scattering (GIWAXS), reveals that Langmuir–Blodgett deposited films have a higher concentration of the ferroelectric β-phase crystals, and that these films are highly oriented with respect to the substrate. Based on these observations, we suggest alternative means of deposition, which may substantially enhance the electrocaloric effect in P(VDF–TrFE) films. This development has significant implications for the potential use of P(VDF–TrFE) in solid-state refrigeration.